GBT440 increases haemoglobin oxygen affinity, reduces sickling and prolongs RBC half‐life in a murine model of sickle cell disease. (5th July 2016) - Oksenberg, Donna; Dufu, Kobina; Patel, Mira P.; Chuang, Chihyuan; Li, Zhe; Xu, Qing; Silva‐Garcia, Abel; Zhou, Chengjing; Hutchaleelaha, Athiwat; Patskovska, Larysa; Patskovsky, Yury; Almo, Steven C.; et al.
Summary: A major driver of the pathophysiology of sickle cell disease (SCD) is polymerization of deoxygenated haemoglobin S (HbS), which leads to sickling and destruction of red blood cells (RBCs) and end‐organ damage. Pharmacologically increasing the proportion of oxygenated HbS in RBCs may inhibit polymerization, prevent sickling and provide long term disease modification. We report that GBT440, a small molecule which binds to the N‐terminal α chain of Hb, increases HbS affinity for oxygen, delays in vitro HbS polymerization and prevents sickling of RBCs. Moreover, in a murine model of SCD, GBT440 extends the half‐life of RBCs, reduces reticulocyte counts and prevents ex vivo RBC sickling. Importantly, oral dosing of GBT440 in animals demonstrates suitability for once daily dosing in humans and a highly selective partitioning into RBCs, which is a key therapeutic safety attribute. Thus, GBT440 has the potential for clinical use as a disease‐modifying agent in sickle cell patients. Abstract : This article is cited in the Editorial Comment published in issue 174:4 (http://onlinelibrary.wiley.com/wol1/doi/10.1111/bjh.14212/full ).